PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN METODE DRILL DI KELAS IV E SEKOLAH DASAR - Rointan Simare Mare; Bistari Bistari; Siti Halidjah (Universitas Tanjungpura, 2021)
Abstract This study aims to describe the improvement of mathematics learning results through the application of google meet assisted drill method in grade IV E SD 34 South Pontianak. Research method used is action research with a form of class action research. Data collection techniques used in the form of interviews, observations and documentation. Data analysis conducted in the form of average calculation data analysis and qualitative data analysis in the form of data collection, data reduction, data presentation and data verification. Data collection instruments in the form of observation sheets, interview sheets and documentation. The results of the study are as follows; The teacher planning phase makes learning tools include RPP, LKPD and learning media that support the implementation of drills; Teachers carry out learning by applying drill methods in two cycles that contain exercises to students; The learning outcomes of the first cycle students 93.54% of students got a score above completion, while in cycle II 96.77% of students got a score above completion; The student's response to the implementation of the drill carried out by the teacher is that the student feels interested because by repeating the exercise the student feels more quickly understood. Keywords: Improvement, Math Learning Outcomes, Drill Method